FAKTOR – FAKTOR YANG MEMPENGARUHI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA DI KOTA PONTIANAK - admin, MAURISIUS RIO RIKYANTO B11108092 (Jurnal Manajemen Update, 2016)
This study aims to determine whether there is influence between attitudes and behavior of consumers on purchasing decisions YAMAHA motorcycle in the town of Pontianak. As for the issue of this study is whether the brand awareness, consumer attitudes, consumer behavior and their loyalty to the purchasing decision either simultaneously or each - each variable. In this study, data were collected through questionnaires to 100 respondents motorcycle YAMAHA product users in the town of Pontianak by using purposive sampling method to determine the respondents to each variable. Then performed an analysis of the data-data that is obtained in the form of analysis, quantitative and qualitative analysis. Quantitative analysis includes the validity and reliability test, test classic assumptions, hypothesis testing through F test and test analysis of the coefficient of determination (R2). Data analysis technique used is multiple linear regression analysis which serves to prove the hypothesis of the study. The data - data that has met the validity, reliability, and classical assumption. Results of the analysis found that four factors of brand awareness, consumer attitudes, consumer behavior, and loyalty they have a positive and significant impact on purchasing decisions. Hypothesis testing using t test showed that four independent variables studied was shown to significantly influence the purchase decision is independent. Then through the F test can be seen that the variable brand awareness, consumer attitudes, consumer behavior, and loyalty they have significant influence on the purchase decision. Keywords: Awareness brand , consumer attitudes, consumer behavior, brand loyalty and purchasing decisions.